Impact analysis of the transponder time delay on radio-tracking observables. Issue 1 (1st January 2018) - Bertone, Stefano; Le Poncin-Lafitte, Christophe; Rosenblatt, Pascal; Lainey, Valéry; Marty, Jean-Charles; Angonin, Marie-Christine
Abstract: Accurate tracking of probes is one of the key points of space exploration. Range and Doppler techniques are the most commonly used. In this paper we analyze the impact of the transponder delay, i . e . the processing time between reception and re-emission of a two-way tracking link at the satellite, on tracking observables and on spacecraft orbits. We show that this term, only partially accounted for in the standard formulation of computed space observables, can actually be relevant for future missions with high nominal tracking accuracies or for the re-processing of old missions. We present several applications of our formulation to Earth flybys, the NASA GRAIL and the ESA BepiColombo missions.